OVERVIEW OF CONTEMPORARY ISSUES OF SUSTAINABLE RURAL DEVELOPMENT IN RUSSIA IN TERMS OF EXISTING DIFFERENCES BETWEEN REGIONS - Ivolga, Anna (Economics of Agriculture, 2014)
Paper includes analysis of current state in the sphere of sustainable rural development in the regions of Russia. Analysis included the set of indicators such as number of rural people, number of rural settlements, rates of births and mortalities, natural and migration increases and declines of population, rates of employment and unemployment, average monthly nominal per capita wages, and level of the subsistence minimum. Indicators have been measured separately for rural and urban areas; regions have been grouped in relation to the particular indicator. As a result, 82 regions have been grouped into aggregations according to their common characteristics and values of studied indicators. Such classification let to compare derived levels of rural development in particular regions, to analyze gaps between rural and urban areas, to discover common threats to sustainable development, and to elaborate local oriented rural policies.